2011
DOI: 10.1590/s0100-06832011000600028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of erosion and deposition on particle size distribution of deposited farmland soils on the chinese loess plateau

Abstract: Particle size distribution (PSD) in the soil profile is strongly related to erosion, deposition, and physical and chemical processes. Water cycling and plant growth are also affected by PSD. Material sedimented upstream of the dam constructions formed large areas of deposited farmland (DF) soils on the Chinese Loess Plateau (CLP), which has been the site of the most severe soil erosion in the world. Two DFs without tillage on the CLP were chosen to study the combined effect of erosion and check dams on PSD. Ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 12 publications
2
5
0
1
Order By: Relevance
“…It is found that the grain size of 0.2-0.6 mm range is the most susceptible to soil erosion. The result of this study is in good agreement with the previous study [27].…”
Section: Effect Of Grain Size Distribution On the Erosion Of The Soilssupporting
confidence: 93%
“…It is found that the grain size of 0.2-0.6 mm range is the most susceptible to soil erosion. The result of this study is in good agreement with the previous study [27].…”
Section: Effect Of Grain Size Distribution On the Erosion Of The Soilssupporting
confidence: 93%
“…These included extensive areas with indicating sheet-flow erosion, as well as the sporadic occurrence of rills, which ind erosion. Surface processes are known to cause size-sorting of soil particles, with t and faster redistribution (sorting out) of the smaller-sized fractions [31]. Howev was not affected by treatment, with similar contents of sand (33.1 ± 1.1%), silt (49.…”
Section: Below-ground Processesmentioning
confidence: 91%
“…Soil silt and clay contents differed significantly between sites (F = 5.943, P = 0.020). This could be due to differences in soil formation but may also be caused by a preferential loss of fine fractions upon erosion (Zhao et al 2011). Sand content increases upon soil erosion after forest conversion and, hence, can be used as an indicator for evaluating soil degradation (Ayoubi et al 2011).…”
Section: Sand Silt and Clay Contentsmentioning
confidence: 99%